La caución como garantía de la persona procesada y el principio de proporcionalidad - Bryan Joel, Mera Avendaño (2021)
ABSTRACT The Organic Crime Law has established several precautionary measures applicable within the criminal process that ensure the attendance of the person who is processed in a trial, among which we have preventive detention that must be used as a last resort in the criminal field, the incumbent of the Criminal action may request for preventive detention, for which it must be properly justified and the judge may or may not grant it. The Organic Crime Law has foreseen that preventive detention can be replaced by the legal figure of caution, which will fulfill the same objective of preventive detention, but it provides the processed person the opportunity to defend himself in freedom. The purpose of this research project is to determine the setting of caution as a right of the processed person and his/her relationship with the principle of proportionality, the setting of the caution may be requested by the judge at the arraignment, it must be justified that he/she is not in none of the inadmissibilities established by the Organic Crime Law, at the same time the technical defense may request a precautionary measure substitution audience based on article 521 of the same legal code. The setting of the caution is closely related to the principle of proportionality since the crime for which the person sanctioned must be considered, the full reparation and the fine that will be imposed to the processed person, so that the legal figure complies with the objective of preventive detention. Keywords: precautionary measures, caution, principle of proportionality. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301